Farming While Aging: Reasons and Strategies for Maintaining Family Farming in Parbotihan Village, North Sumatera - Marbun, Firdaus (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
One of the challenges for farming sustainability and food security into the future is the aging of farmers. The reluctance of youth to work in farming and their choice to migrate to urban areas has resulted in a scarcity of productive workers in rural areas. As a result, farming production relies on aging farmers. The implications of this condition not only have an impact on decreasing farming productivity but also to the family farming sustainability and threats of food security in the future. Apart from the impact on decreased production, it is important to see how aging farmers overcome their limited capabilities by rely on farming as a source of their daily needs. This research aimed to explain the impact of migration of rural youth for family farming’s sustainability and what strategies that aging farmer carried out to maintain their farm when they become the main actors in farming. This research was conducted on rice farmers in the village of Parbotihan, North Sumatra using qualitative methods and data collection techniques through observation and in-depth interviews. The findings in this study are that the reluctance of rural youth to work in farming is influenced by society’s negative view of farming. This negative view encourages rural youth migrate to urban areas and leave their family farming for their parents who have limited capabilities yet still fulfil their needs. In the end, farmers made efforts to overcome their limitations in several ways, such as setting a more flexible planting schedule, choosing the type of crop, and maintaining the season once a year.